THE INFLUENCE OF COMPASSION ON CHARACTER DEVELOPMENT: A STUDY ON THE CHARACTER OF THE CHILD IN STEPHEN CRANE’S SHORT STORY “A DARK BROWN DOG” - Silvia Hany Arnelyantoro; Dina Isnaini Hanifah; Nadiyah Rahmatul Ummah (Cahaya Ilmu Bangsa Institute, 2024)
This study explores the profound impact of compassion on the character development of the child in Stephen Crane's